2010
DOI: 10.2174/156720510792231720
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Alzheimers Disease from EEG Signals: Where Are We Standing?

Abstract: This paper reviews recent progress in the diagnosis of Alzheimer's disease (AD) from electroencephalograms (EEG). Three major effects of AD on EEG have been observed: slowing of the EEG, reduced complexity of the EEG signals, and perturbations in EEG synchrony. In recent years, a variety of sophisticated computational approaches has been proposed to detect those subtle perturbations in the EEG of AD patients. The paper first describes methods that try to detect slowing of the EEG. Next the paper deals with sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
204
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 390 publications
(221 citation statements)
references
References 200 publications
(354 reference statements)
17
204
0
Order By: Relevance
“…• Monitor alertness, coma and brain death [54,55] • Locate areas of damage following head injuries [56,57], stroke [58,59] or brain haemorrhage [60,61] • Detect Alzheimer's disease [62][63][64][65] and brain tumours [66,67] • Investigate sleep disorders [68,69] and epilepsy [70,71] • Monitor human brain development [72,73] • Measure the depth of anaesthesia [74] • Test the effect of drugs [75,76].…”
Section: Electroencephalogram (Eeg)mentioning
confidence: 99%
“…• Monitor alertness, coma and brain death [54,55] • Locate areas of damage following head injuries [56,57], stroke [58,59] or brain haemorrhage [60,61] • Detect Alzheimer's disease [62][63][64][65] and brain tumours [66,67] • Investigate sleep disorders [68,69] and epilepsy [70,71] • Monitor human brain development [72,73] • Measure the depth of anaesthesia [74] • Test the effect of drugs [75,76].…”
Section: Electroencephalogram (Eeg)mentioning
confidence: 99%
“…Many studies have shown that the EEG of AD patients has an abnormal spectrum [3,6,10,13,15,[19][20][21]. In particular, the EEG signals of AD patients tend to "slow down": they contain more power in low-frequency bands compared to healthy age-matched subjects.…”
Section: A Feature Extractionmentioning
confidence: 99%
“…To date, the classification performance of these algorithms is about 80%-90% [5], and hence there is still significant room for improvement. A promising strategy to improve the diagnostic power of EEG for AD is to carefully design and optimise time-domain and frequency-domain EEG features [6]. We follow that approach in this paper: we investigate the use of relative power within different EEG frequency bands as a feature to distinguish mild AD from healthy control subjects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…• Monitor alertness, coma and brain death [2,3] • Locate areas of damage following head injuries [4,5], stroke [6,7] or brain haemorrhage [8,9] • Detect Alzheimer's disease [10][11][12][13] and brain tumour [14,15] • Investigate sleep disorders [16,17] and epilepsy [18,19] • Monitor human brain development [20,21] • Measure the depth of anaesthesia [22] • Test drug effects [23,24] Both the progressive developments in electrical engineering and the fascination with the human brain have attracted researchers from different background to investigate EEG recordings.…”
Section: Introductionmentioning
confidence: 99%